The use of supplementary materials in EFL classes: a comparative analysis of public and private high schools - Arévalo Ruiz, Soraya Katherine (2012)
The present research explored The Use of Supplementary Materials in EFL Classes: a Comparative Analysis of Public and Private High Schools. The main purpose of this research was to determine, analyze and compare the supporting materials used in public and private high schools. This research was conducted in Loja, Ecuador. The sample included one public and one private high school. The participants were constituted by students and teachers who belonged to the 1st, 2nd and 3rd years of senior high school in each institution. Qualitative and quantitative approaches were utilized in this study. The qualitative analysis considered pertinence, appropriateness and quality of the used materials and examined whether they supplied or not the requirements of the different learning styles. The quantitative analysis compared the results of both high schools as well as the frequency of their use in each year. This study revealed that supplementary materials were mostly employed in the public high school where their use and elaboration resulted to be more pertinent, appropriate and qualified, helping teachers to reach their objectives and making their EFL classes more interesting and motivating